2008
DOI: 10.1007/s00709-008-0303-1
|View full text |Cite
|
Sign up to set email alerts
|

Expansins and coleoptile elongation in wheat

Abstract: Expansins are now generally accepted to be the key regulators of wall extension during plant growth. The aim of this study was to characterize expansins in wheat coleoptiles and determine their roles in regulating cell growth. Endogenous and reconstituted wall extension activities of wheat coleoptiles were measured. The identification of beta-expansins was confirmed on the basis of expansin activity, immunoblot analysis, and beta-expansin inhibition. Expansin activities of wheat coleoptiles were shown to be se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 33 publications
1
39
0
Order By: Relevance
“…In maize, where EXPBs were firstly identified as group-1 grass pollen allergens, some EXPBs (e.g., Zeam1) are known to play a role in pollen tube penetration (Cosgrove et al 1997), while others (e.g., ZmEXPB2) appear to take part in root elongation (Kam et al 2005). Root-specific/preferred EXPBs have also been isolated from barley (HvEXPB1), wheat (TaEXPB23), rice (OsEXPB5), Arabidopsis (AtEXPB1), and soybean (GmEXPB1, GmEXPB2, and GmEXPB6) (Kwasniewski and Szarejko 2006;Gao et al 2008;Kwon et al 2008;Won et al 2010;Li et al 2011Li et al , 2013. The root-specific activity of HvEXPB1 from barley and OsEXPB5 from rice has been shown to be conferred by root hair specific cis-elements (RHEs) (Won et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In maize, where EXPBs were firstly identified as group-1 grass pollen allergens, some EXPBs (e.g., Zeam1) are known to play a role in pollen tube penetration (Cosgrove et al 1997), while others (e.g., ZmEXPB2) appear to take part in root elongation (Kam et al 2005). Root-specific/preferred EXPBs have also been isolated from barley (HvEXPB1), wheat (TaEXPB23), rice (OsEXPB5), Arabidopsis (AtEXPB1), and soybean (GmEXPB1, GmEXPB2, and GmEXPB6) (Kwasniewski and Szarejko 2006;Gao et al 2008;Kwon et al 2008;Won et al 2010;Li et al 2011Li et al , 2013. The root-specific activity of HvEXPB1 from barley and OsEXPB5 from rice has been shown to be conferred by root hair specific cis-elements (RHEs) (Won et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In a resurrection plant, Craterostigma plantagineum, the increase in expansin activity was accompanied by the enhancement of wall extensibility during dehydration and rehydration processes, suggesting a role of expansin proteins in increasing wall flexibility and promoting leaf growth under drought stress (Jones and McQueen-Mason 2004). In our previous report, drought stress was shown to induce the expression and activity of expansin protein in wheat coleoptiles (Gao et al 2008;Zhao et al 2011). Over-expression of an expansin gene TaEXPB23 from wheat enhanced the drought tolerance in transgenic tobacco (Li et al 2010).…”
Section: Introductionmentioning
confidence: 95%
“…To measure endogenous expansin activity, acid-induced cell wall extension was performed according to the methods described by Cosgrove (1989) and Gao et al (2008). Coleoptiles were abraded with carborundum and squeezed between two glass slides to remove cell sap.…”
Section: Detection Of Acid-induced Cell Wall Extensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three up-regulated genes putatively associated with cell wall expansion in mETR1asLOX3 leaves were further analyzed by quantitative real-time (qRT)-PCR using leaf samples collected at 0, 6, 20, and 60 h after W+OS treatment. Pectin methylesterase (+2.7-fold change; BP131988) and expansin (+1.9-fold change; BP531140), previously shown to mediate cell expansion in other plant species (Micheli, 2001;Pien et al, 2001;Gao et al, 2008), showed more abundant transcripts in mETR1asLOX3 compared with wildtype and remaining transgenic lines (Fig. 6).…”
Section: Transcriptional Changes In Metr1aslox3 Leavesmentioning
confidence: 99%